Jalal al-Din Rumi & Human Transformation: How to Capture a Wild Elephant - Crow, Karim Douglas (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2012)
Through verse, music and dance the Mawlavi Order sought to perpetuate the energy of Rumi’s personality and impact of his enlightening insight. Rumi strove to make possible a vertical opening of consciousness within his followers, thereby facilitating fragile possibilities for human transformation. Soul with its innermost focus of attentive–awareness forms the only foundation for expanding our understanding of the cosmos, and for attaining what is possible for Man. We reflect on how Rumi might apprehend our current realities, and what has become of human transformation in our era of psycho–somatic physicalism. Our meditation is intended to provide food for thought, as well as enliven the heart. We are looking for Rumi. we are still looking for him. We are seeking him – and Rumi is seeking us! Rumi had his own epitaph inscribed upon his tomb: “When we are dead seek not our tomb in the earth, but find it in the hearts of men.” is where we There have to look for Rumi: within the Hearts of men – and the hearts of women and girls and boys. His voice echoes loud and clear for those persons who have ears to hear, and who have learned how to listen .